Can team-sport athletes accurately run at submaximal sprinting speeds? implications for rehabilitation and warm-up protocols - Darrall-Jones, J.; Roe, G.; Cremen, E.; Jones, B. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study is to examine the ability of team-sport athletes to accurately run at a range of submaximal sprint velocities (60-90% maximal velocity; Vmax) under verbal instruction without any objective feedback. Twelve professional male rugby union players (age 19.7 ± 0.9 years, body mass 98.3 ± 13.9 kg, height 184.0 ± 7.5 cm) were verbally instructed to complete three 40-m sprints at each of 60, 70, 80, and 90% of Vmax in a randomized order. Percentage Vmax achieved during each sprint was compared with criterion velocities calculated from Vmax testing undertaken a week prior. Players underestimated (ran faster) their sprint velocity when asked to run at 60% (very large to extremely large mean bias, 23%; range, 57-88% Vmax), 70% (large to very large, 11%; 67-93% Vmax), and 80% (small, 2%; 71-91% Vmax) of their Vmax, whereas overestimated (ran slower) their sprint velocity when asked to run at 90% Vmax (moderate, -4%; 77-95% Vmax). Team sport players may require objective feedback when performing submaximal sprinting to ensure that velocities achieved are similar to those prescribed. This may be particularly important where graded exposure to maximum velocities is required, for example during rehabilitation or warm-ups.